Engineering of plasmid vectors for enhancing agrobacterium-mediated plant transformation - Teo, Yuh Leng (2022)
Agrobacterium-mediated transformation (AMT) is the most widely used approach for plant transformation due to its ease of application and low cost. However, only limited crop plants can be consistently transformed with high efficiency. The bottleneck of the AMT approach lies in the low-copy tumourinducing (Ti) plasmid that limits the expression of virulence genes. Furthermore, helper plasmids that can enhance the AMT efficiency are not commercially available, thus constraining the advancement in plant transformation. This project aimed to enhance the overall plant transformation efficiency by constructing a broad host range (BHR) expression vector to express the key regulatory virulence genes of Agrobacterium tumefaciens and a miniaturized helper Ti plasmid to harbour the essential virulence genes. First, the BHR expression vector (pYL101C) was constructed via Golden Gate cloning, including ColE1 and pBBR1 ori, a GmR selectable marker, a strong constitutive integron promoter (PINTc) followed by a multiple cloning site downstream for facile gene cloning. As for the miniaturized helper Ti plasmid, plasmid pYL102 was constructed based on plasmid pCAMBIA5105, using long PCR amplification and homologous recombination. As a result, the size of pYL102 was reduced to 30.6 kb, which is a ~40% reduction of pCAMBIA5105. To test the functionality of the constructed vector system, a key virulence gene for AMT, virG-N54D, was cloned into pYL101C to produce pYL101C::virG-N54D and was electroporated into the A. tumefaciens C58C1 strain together with the binary vector pGWB2::e35S-sfGFP and pYL102 for transient plant transformation. Two days after agroinfiltration of Nicotiana benthamiana leaves, strong green fluorescence was observed on spots infiltrated with the positive control and test Agrobacterium harbouring the constructed ternary vector system, but not in the mock-infiltrated leaves. The fluorescence intensity from the test agroinfiltrated leaves was significantly higher than those of the mock-infiltrated leaves (p<0.01), indicating that the constructed vector system is functional in plant transformation and can be utilized to increase transformation efficiency.